Cognitive flexibility training for chronic pain: a randomized clinical study - Katherine J. Holzer; Marko S. Todorovic; Elizabeth A. Wilson; Aaron Steinberg; Michael S. Avidan; Simon Haroutounian (PAIN Reports, 2024)
Abstract. Introduction:. Previous studies suggest an association between cognitive flexibility and development of chronic pain after surgery. It is not known whether cognitive flexibility can be improved in patients with chronic pain. Objectives:. This study tested whether a neurocognitive training program results in improved cognitive flexibility and pain in patients with chronic pain. Methods:. We conducted a single-center, prospective, randomized study investigating 5-week daily neurocognitive training in patients with chronic pain. Participants (n = 145) were randomized into neurocognitive training or care as usual, and they completed assessments at baseline, posttreatment, and 3 months. The treatment group was asked to spend 35 minutes daily completing a program with tasks on cognitive flexibility, memory, attention, and speed. The primary outcome was performance on the neurocognitive performance test (NCPT). Secondary outcomes included levels of pain interference and severity. Results:. At 5 weeks, the treatment group showed greater improvements on NCPT compared with the control group (d = 0.37); effect size was smaller at 3 months (d = 0.18). The treatment group reported lower pain severity at 5 weeks (d = 0.16) and 3 months (d = 0.39) than the control group, but pain interference was only lower at 3 months (d = 0.20). Conclusions:. Outcomes suggest that using neurocognitive training to modify cognitive flexibility in patients with chronic pain may improve pain severity. This study provided effect size estimates to inform sample size calculations for randomized controlled trials to test the effectiveness of neurocognitive interventions for the prevention and treatment of chronic pain.